ANALYSIS OF BUILDING BEAMS CALCULATION FOR EMPLOYEE MESS IN KONAWE SOUTHEAST SULAWESI - GIFTY CAHYANI; LYDIA DARMIYANTI; GALI PRIBADI (CV KULTURA DIGITAL MEDIA, 2024)
Buildings are certainly planned with the concept of earthquake-resistant buildings. In this research, the author concentrates on one of the structural elements, namely the beam which is reviewed for its structural behavior, by calculating the earthquake area to analyze the beam reinforcement. The analyzed building is located in Sulawesi, the building structure used is a reinforced concrete structure, analyzing only the upper structure, and not analyzing the lower structure which refers to the Indonesian National Standard Regulations including SNI 1726-2019 concerning Procedures for Earthquake Resistance Planning for Building and Non-Building Structures, SNI 2847-2019 concerning Structural Concrete Requirements for Buildings, and SNI 1727-2020 concerning Minimum Design Loads and Criteria. In this final project, structural modeling and analysis were carried out using Etabs20 software. From this study, the largest internal force on the structure of the employee mess building in Konowe, Beam (200x400) on the 2nd floor, with a maximum moment value of 111.554 kNm and a maximum field moment of 53.1946 kNm, shear force of 100.6759 kN. Based on the force in the Etabs output, the beam (200x400) requires 5-D16 pedestal top reinforcement, 3-D16 pedestal bottom reinforcement, 2-D16 top field reinforcement, 3-D16 bottom field reinforcement, D10-100 pedestal stirrup, D10-125 field stirrup. The reinforcement calculation is in accordance with SNI 2847-2019. It is recommended to compare the results of the ETABS analysis with the results of manual calculations based on SNI 2847: 2019. This comparison will provide an overview of the accuracy and reliability of ETABS software in calculating the reinforcement ratio.